A comparison of the intra-cyclic velocity variation in breaststroke swimmers with flat and undulating styles - Colman, V.; Persyn, U.; Daly, D. (Journal of Sports Sciences, 1998)
The aim of this study was to establish differences in intra-cyclic horizontal velocity variation of the body's centre of mass in breaststroke swimmers with flat and undulating styles. Vertical eel-like body waving and trunk rotations were measured to distinguish styles. To reconstruct trunk extension and kyphosis in the poorly visible zone close to the water surface, a semi-automated video-analysis system was developed. From 45 international-level swimmers examined, two groups of women and two groups of men were identified, those using the most undulating and those using the flattest styles. Among the men with the flattest style, the maximum and minimum horizontal velocity of the body's centre of mass differed by 76% from the mean swimming velocity; among the women with the most undulating style, the figure was 53%. In the most undulating style, less horizontal velocity variation of the body's centre of mass could be explained by movements of the body parts above the water surface, creating a transfer of momentum: a quick backward upper trunk rotation generates resistance and a quick forward shoulder girdle and upper arm movement, followed by a quick forward upper trunk and head rotation, generates propulsion. In addition, during an upward leg kick, some swimmers generated propulsion similar to that seen in eels.